Flow Analysis of Conclad Extrusion with Two Wheels. (2015) - Hoshino, M.; Murata, S.
Abstract: Conclad extrusion using one wheel with two grooves was developed from Conform continuous extrusion and is used to manufacture trolley wire for Japanese trains. On the other hand, we developed Conclad extrusion with two wheels and investigated metal flow in this process by model experiment. Conclad extrusion with two wheels had two clear advantages over the use of one wheel with two grooves, namely there was a decrease in the content of dead metal in the chamber and the flow conditions were more appropriate for bonding. It is clear that bonding condition is good in case that abutment angle is 60°.